The role of microbial factor in the genesis of chronic endometritis - Yu. A. Petrov (Кубанский научный медицинский вестник, 2016)
It was identified that the determination of pathological changes in human immune response in each macrotype of chronic endometritis, microbiological features, б-2-microglobulin of fertility in serum are prognostic indicators of structural and functional changes of the endometrium in different variants of chronic endometritis.